Stress less : the new science that shows women how to rejuvenate the body and the mind - Singer, Thea. (New York, N.Y. : Hudson Street Press, 2010)
A veteran health and science journalist reveals how stress accelerates the aging process by affecting everything from mood to one's genes and explains how women can reverse the damage.
Stress : the new biological clock : how you can turn it back -- The old science of stress -- The new science of stress - -Your brain on stress -- Stress and diet -- Stress and exercise -- Stress and the mind -- Stress and social support -- Stress and sleep -- I should have danced all night.
Includes bibliographical references (p. [255]-302) and index.
Keywords: Women -- psychology